SureMail: Notification Overlay for Email Reliability - Agarwal, Sharad; Padmanabhan, Venkat; Joseph, Dilip (HotNets IV, 2005)
We consider the problem of silent email loss in the Internet. Some recent studies have reported loss rates of 0.5-1%, which indicates that the problem is significant, especially since email loss can impose a high cost. We present SureMail, a system designed to address the silent email loss problem. SureMail augments the existing SMTP-based email system with a notification overlay to make intended recipients aware of email they might be missing. Our design addresses several challenges including avoiding dependence on support from the email infrastructure, placing minimal demands on users, preventing spammers from subverting the system, and maintaining the privacy of users.